MMPs are required for recruitment of antigen-nonspecific mononuclear cells into the liver by CTLs - Sitia, Giovanni (American Society for Clinical Investigation, 2004)
We recently showed that antigen-nonspecific inflammatory cells are recruited into the liver when hepatitis B virus (HBV)-specific CTLs are injected into HBV transgenic mice, and that this process amplifies the severity of liver disease. We also showed that the severity of CTL-induced liver disease is ameliorated by the depletion of Gr-1(+) cells (Gr-1 is an antigen highly expressed by neutrophils), which, secondarily, abolishes the intrahepatic recruitment of all antigen-nonspecific Gr-1(–) mononuclear cells (NK and NKT cells, T and B lymphocytes, monocytes, macrophages, dendritic cells) despite the strong induction of chemokine gene expression. Those results suggested that in addition to chemokine expression, CTL-induced functions are necessary for mononuclear cell recruitment to occur. We now report that MMPs known to be produced by Gr-1(+) cells are rapidly induced in the livers of CTL-injected mice. The inhibition of MMP activity reduced the intrahepatic recruitment of antigen-nonspecific mononuclear cells and much of the attending liver disease without affecting the migration or antiviral potential of antigen-specific CTLs. The notion that the inhibition of MMP activity is associated with maintenance of antiviral effects but diminished tissue damage may be significant for the development of immunotherapeutic approaches for the treatment of chronic HBV infection.